Comparison of Nifedipine and Captopril for the Control of Hypertension among Children with Acute Glomerulonephritis: A Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: As control of hypertension is crucial in patients with acute glomerulonephritis (AGN) to avoid life-threatening complications and deaths.Objectives: This study was done to see the efficacy of captopril and nifedipine to control hypertension in AGN in respect to their clinical response, duration and cost of treatment.Methodology: This randomized clinical trial was done among children ages ranging from 3 to 12 years who were suffering from AGN with hypertension and/or its complications. After enrolment the patients were randomly divided into two groups as Group A and Group B. Both groups received the standard management of AGN. In addition, children in group-A received captopril (dose 0.5 up to 6 mg/kg/day) and children in group B received nifedipine (0.25 up to 0.5 mg/kg/day). Their effectiveness in relation to timing of response, duration of therapy, side effects and cost effectiveness of the drugs were assessed statistically and at p value of